Should Israel screen all mothers-to-be to prevent early-onset of neonatal group B streptococcal disease? A cost-utility analysis - Ginsberg Gary M; Eidelman Arthur I; Shinwell Eric; Anis Emilia; Peyser Reuven; Lotan Yoram (BMC, 2013)
Abstract Background In Israel, an average of 37 children are born each year with sepsis and another four with meningitis as a result of Group B Streptococcal (GBS) disease. Israel currently only screens mothers with defined risk factors (around 15% of all pregnancies) in order to identify candidates for Intrapartum Antiobiotic Prophyhlaxis (IAP) of GBS. This paper presents a cost-utility analysis of implementing an alternative strategy, which would expand the current protocol to one aiming to screen all pregnant women at 35-37 weeks gestation based on taking a vaginal culture for GBS. Methods A spreadsheet model was built incorporating technical, epidemiological, health service costs, demographic and economic data based primarily on Israeli sources. Results The intervention of universal screening (compared with the current scenario) would increase screening costs from 580,000 NIS to 3,278,000 million NIS. In addition, the intervention would also increase penicillin costs from 39,000 NIS to 221,000 NIS. Current culture screening of approximately 15% of mothers-to-be with high risk factors resulted in 42 GBS births in 2008-9 (0.253/1000 births). Expanding culture screening to 85% of mothers-to-be, will decrease the number of GBS births to 17.3 (0.104/1000 births). The initial 2.9 million NIS incremental intervention costs are offset by decreased treatment costs of 1.9 million NIS and work productivity gains of 811,000 NIS as a result of a decrease in neurological sequelae from GBS caused meningitis. Thus the resultant net cost of the intervention is only around 134,000 NIS. Culture based screening will reduce the burden of disease by 12.6 discounted Quality Adjusted Life Years (QALYS), giving a very cost effective baseline incremental cost per QALY (cf. risk factor screening) of 10,641 NIS per QALY. The data was very sensitive to rates of anaphylactic shock and changes in the percentage of meningitis cases that had associated long term-sequelae. Conclusion It is recommended that Israel adopt universal culture-based GBS screening.